2019
DOI: 10.1111/ceo.13567
|View full text |Cite
|
Sign up to set email alerts
|

Prospective two‐year study of clinical outcomes following epithelium‐off pulsed versus continuous accelerated corneal crosslinking for keratoconus

Abstract: Importance Keratoconus is a debilitating condition with a disproportionately high impact on health resources and vision‐specific quality of life. Background This study aimed to compare 2‐year outcomes of epithelium‐off pulsed (p‐ACXL) and epithelium‐off continuous (c‐ACXL) accelerated corneal crosslinking in progressive keratoconus. Design Prospective, interventional case series. Participants Eighty eyes of 80 patients were included. Methods The visual, refractive and tomographic results of the two crosslinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…In their paper, Ziaei et al found that the continuous A‐CXL cohort achieved a greater mean reduction in both manifest refraction and maximum keratometry compared to the patients who received pulsed CXL. The difference was statistically significant albeit there remained some variation in the outcomes . The impact on best‐corrected visual acuity was positive for both groups; however, this did not appear to translate into a clinically significant change over the course of extended follow‐up matching existing meta‐analyses .…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…In their paper, Ziaei et al found that the continuous A‐CXL cohort achieved a greater mean reduction in both manifest refraction and maximum keratometry compared to the patients who received pulsed CXL. The difference was statistically significant albeit there remained some variation in the outcomes . The impact on best‐corrected visual acuity was positive for both groups; however, this did not appear to translate into a clinically significant change over the course of extended follow‐up matching existing meta‐analyses .…”
mentioning
confidence: 73%
“…This is significant because the risks of additional retreatment on long‐term corneal health are largely unknown. Our lack of understanding of the impact of surgical variables is readily identified by Ziaei et al and was confirmed recently in a further study by Lang et al They found little correlation between the change in measured variables and corrected vision . Indeed, we cannot be sure whether long‐term evaluation of keratoconic treatment outcomes reflects the impact of the treatment or simply the influence of the regular age‐related corneal stiffening process .…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Initially, visual acuity can be corrected with spectacles or contact lenses. Corneal cross‐linking utilizes a photochemical reaction between the riboflavin and ultraviolet A (UV‐A) in the corneal stroma and has been reported to arrest the progression of the disease, but in cases of advanced keratoconus, corneal transplantation may be required to improve vision . Penetrating keratoplasty (PKP) was the earliest transplant technique used to treat keratoconus, and remains the mainstay for managing late‐stage disease in many countries .…”
Section: Introductionmentioning
confidence: 99%